Rancang Bangun Tungku Gasifikasi Tipe Counter-Flow dengan Bahan Bakar Biomassa Municipal Solid Waste (MSW) - Dendi Adi Saputra; Adjar Pratoto; Andoni Prayogi (METAL: Jurnal Sistem Mekanik dan Termal, 2017)
This research discusses about designing of counter-flow type gasification stove utilizing biomass municipal solid waste (MSW). The first step of the research process is to formulate the design concept of the gasification stove using the MSW collected in Padang city. The results of the design concept formulation are used to obtain the detail design parameters which is used as the reference for manufacturing the stove. The main designing parameters of the gasification stove are the diameter and the height of the stove. The technical drawing is made according to the designing parameters obtained from the design concept formulation. Base on the technical drawing, the counter-flow type biomass gasification stove was built. The obtained results show that for a large value of updraft air and a small value of downdraft air, the operating time of the stove is long. This condition is obtained in the case of standard air and fuel ratio (AFR<1.5). This results show that the gasification stove efficiency is better in comparison with the conventional one.